Sports injury epidemiology: foundation of evidence of, by, and for athletic trainers - McKeon, J. M. M.; McKeon, P. O.; Nedimyer, A. K. (Journal of Athletic Training, 2021)
Almost 15 years ago, the first epidemiology studies based on National Collegiate Athletic Association (NCAA) injury-surveillance data were published in the Journal of Athletic Training. In these reports, researchers detailed the injury rates and trends that occurred in intercollegiate athletics. The purpose of these reports was to provide the basis for athletic trainers to advance the recognition, rehabilitation, and prevention of injuries and illnesses related to athletic participation. Having a robust understanding of the foundational aspects of epidemiology is necessary for the ability to read, critique, and incorporate epidemiologic evidence into clinical practice, education, and research. The purpose of this commentary is to provide a brief overview of how to consume and critique epidemiology research, including a review of basic concepts, how to critically appraise the methods and results of epidemiology research, and how to apply epidemiology research to clinical practice, education, and research.